Griscelli syndrome type 2: a tragic tale of two siblings - Muppalla, Mowlika; Parimi, Vijaya Prasanna; Tejaswini, R. N.; Vaishnavi, Ambavaram; Ranganath, Prajnya; Lanka, Naveen Kumar (International Journal of Contemporary Pediatrics, 2025)
Griscelli syndrome (GS) is a rare autosomal recessive disorder classified as an inborn error of immunity. Among its three variants, GS type 2, caused by mutations in the RAB27A gene, is marked by partial albinism and recurrent episodes of hemophagocytic lymphohistiocytosis (HLH). This case report chronicles the poignant journey of two siblings tragically lost to this condition. GS type 2 carries a high mortality rate, primarily due to HLH complications. Currently, hematopoietic stem cell transplantation (HSCT) remains the sole curative treatment for this devastating syndrome.